Emerging roles of eraser enzymes in the dynamic control of protein ADP-ribosylation - Julia O’Sullivan (Nature Portfolio, 2019)
ADP-ribose erasing enzymes are increasingly recognized as critical regulators of protein ADP-ribosylation dynamics in living systems. Here, the authors review recent advances in the discovery and characterization of ADP-ribose erasers and discuss their role within the cellular ADP-ribosylation machinery.